STUDI PEMANFAATAN DAUN SIRSAK (Annona murica linn.) SEBAGAI MINUMAN SEDUH DENGAN PENAMBAHAN TEH (Camelia sinensis) SEBAGAI MINUMAN FUNGSIONAL: (A study of suorsop leaf utilization as brewed beverage with tea addition as functional drink) - Mulyati M. Tahir; Jumriah Langkong; Anmar Anmar (jurnal1, 2018)
Kepok banana (Musaparadisiaca formatypica) is one fruit that contains enough digestive fiber for the body. Kepok banana (Musaparadisiaca formatypica) is usually processed by frying or steaming, bananas have a short shelf life and easily damaged.Therefore, to extend the shelf life of bananas, fruit will be processed into fruit leather products. However, because the color of bananas are less attractive, the color addition will make the product preferred by consumers. Terungbelanda (Solanum betaceum cav.)has a bright color and has enough fiber content so well processed into fruit leather. The objective of this research was to find the best treatment combination between kepok banana (Musaparadisiaca formatypica) and terungbelanda (Solanum betaceum cav.) sugar concentration to produce a good physical and chemical properties and favored by consumers. The research was also to find out the effect of sugar concentration addition to physical, chemical and organoleptic fruit leather banana and terung belanda (Solanum betaceum cav.). Treatment applied was A1: kepok banana (Musaparadisiaca formatypica) mashed 50%: Terung belanda (Solanum betaceum cav) mashed 45%: sugar 5%; A2: 45%: 40%: 15%; A3: 40%: 35%: 25%. Fruit leather is then tested organoleptically including color, flavor, taste and texture and was chemically tested including moisture content, total acid, pH, anthocyanin and fiber. The result of the research shows that A1 treatment: 50% banana porridge: terung belanda porridge 45%: 5% sugar produces the best fruit leather product in terms of water content, total acid, pH, anthocyanin, fiber, aroma, taste, and texture.